Thermodynamic description of the Mg-O and Al-O systems - Liu, Shuhong; Li, Xiaojing (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Thermodynamic properties of oxides have a significant impact on the corrosion behavior of alloys. MgO and Al2O3 are important products in the corrosion process of Mg-Al alloys, so it is necessary to investigate their thermodynamic properties. The Mg-O and Al-O systems have been critically evaluated and re-assessed by the CALPHAD (CALculation of PHAse Diagram) approach. The liquid phases of these systems were described using the ionic liquid model. According to the literature data, the oxide phases, MgO and Al2O3 were treated as stoichiometric compounds. Thermodynamic parameters of the two stoichiometric compounds were optimized by considering both phase diagram and thermodynamic data and a set of self-consistent thermodynamic parameters was finally obtained for each system. The calculated results using the presently obtained thermodynamic parameters can reproduce the reliable experimental data in the literature reasonably.
Keywords: Mg-O; Al-O; thermodynamic assessment; phase diagram; CALPHAD method